Beberapa Faktor yang Berpengaruh terhadap Kejadian Penyakit Dekompresi pada Penyelam Tradisional (Studi Kasus di Karimunjawa) - Halena Isrumanti Duke; Suharyo Hadisaputro; Sofa Chasani; Anies Anies; Munasik Munasik (Jurnal Epidemiologi Kesehatan Komunitas, 2016)
Background : Decompression sickness is caused by the release and development of gas bubbles in the late phase of blood or tissue due to the rapid pressure drop in the vicinity. Risk factors affected to decompression sympton such as depth, long dive, smoking habit, obesity, alcohol consumption, dehydration, and anemia. The purpose of this study to explain the magnitude of the effect of risk factors on the incidence of decompression sickness in divers traditional.Methods : This is mixed methode study that used a case-control study design is strengthened with indepth interview. Subject of respondents 46 were chosen, including 23 cases and 23 controls were taken by purposive sampling. Research instrument was a questionnaire interview. Analysis of the data using univariate, bivariate (chi-square) and multivariate (logistic regression).Result : Variables that proved to be a risk factor for decompression is the depth of the dive ≥30 meters (OR = 6.62, 95% CI 1059-41390, p = 0.043), longer dives ≥ 2 hours (OR = 61 680,95% CI = 3.687-1031.93, p = 0.004) and anemia (OR = 14,453, 95% CI = 2146-97346, p =0.006). Variables that are not proven to be a risk factor for decompression is smoking, alcohol consumption, and obesity.Conclusions : Factors that influence the incidence of decompression, depth of dive ≥ 30 m, long dive ≥ 2 hours, and anemia with probability 94,45%.